Υποστήριξη θαλάσσιου χωροταξικού σχεδιασμού στην Κύπρο με τη χρήση γεωγραφικών συστημάτων πληροφοριών - Ευσταθίου, Στυλιανός (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
As maritime activities are increasing within the EEZ of Cyprus, the need for an integrated Maritime Spatial Planning (MSP) extends more and more, especially in these times of social and economic decline facing the island. Such a design will attempt to record, analyze and propose differentiations to the current situation of the Cyprus EEZ which is characterized by disorder and disharmony. It will unlock the potential investment and allow operations such as drilling for hydrocarbons, wind farms, fishing, aquaculture, tourism, coastal navigation, the underwater archeology, coexist peacefully, to the benefit of residents and the national economy. This thesis focuses on the marine area between Parekklisia of Limassol and Alaminos of Larnaca District. The main highlights of the European directives issued that are directly related to this topic are presented in detail and subsequently MSP applications in European Union countries and other countries of the world are displayed. Thereafter the activities shown in the study area are divided into three main Axes (routes): Energy, Tourism and Environment. Having made an assessment of the conflicts between the activities of each axle and between the axles, follows the development of three MSP scenarios for the region of study, each oriented towards one of the above axes (routes). Based on the above created scenarios, followed the Analytic Hierarchy Process (AHP) for one of the scenarios created to distribute weight in the activities of the study area. Upon completion of the AHP, there were created zones of influence (Buffer zones) for each activity, supported by approved data and information provided by the Cyprus University of Technology. Finally, after a series of combination and data processing, final maps were exported for the study area combining the results of the AHP method and the results of the zones of influence, suggesting suitable locations for the placement of new activities and indicating all the activity conflicts of the selected scenario.
Keywords: Maritime spatial planning; AHP Scenarios; Geometric Information System; EEZ; Θαλάσσιο χωροταξικό σχεδιασμό; Σενάρια ΑΗP; Γεωγραφικά συστήματα πληροφοριών; ΑΟΖ